Evaluation of seed treatment chemicals for the control of seedling bacterial blight of cowpea in Northern Nigeria - Alabi, O.; Emechebe, A. (Informa UK Limited, 2004)
The effect of metalaxyl + mancozeb (RidomilMz), metalaxyl + carboxin + furathiocarb (Apron plus), metalaxyl + copper-1-oxide (Ridomil plus), benomyl (Benlate), maneb + thiophanate-methyl (Labilite) and zinc + maneb (Mycotrin) on seed germination, incidence and severity of seedling bacterial blight in cowpea induced by Xanthomonas campestris pv vignicola was assessed on the field in the 2000 and 2001 cropping seasons. Zinc + maneb gave the best control and was closely followed by metalaxyl + carboxin + furathiocarb. Others were moderate in their effects except benomyl that was slightly better than the check. The need for appropriate use of seed treatment chemical for the control of bacterial blight is discussed.